The Application of Shipping Governance in the Management of Small E-Pas Outlet in Pangkil Village, Bintan Regency - M. Rizky Indrawan Saputra; Jauzari Helmi; Adrian Kurnia Sobana Putra (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2025)
Indonesia’s position as the world’s largest archipelagic state makes small-scale fishing vessels central to mobility and coastal livelihoods, yet many traditional boats still face uneven access to legality services, safety oversight, and state support conditions that can increase operational risk and exclude fishers from entitlements such as subsidized fuel. This study investigates how shipping governance is applied through the management of a Small E-Pas (e-Pas Kecil) outlet in Pangkil Village, Bintan Regency, and assesses what the outlet’s village-level implementation implies for traditional fishers. Using a qualitative, descriptive case study design, the research draws on systematic document analysis of national regulations and circulars, official institutional releases, and local media reports related to vessel measurement, registration, service delivery, and inter-agency coordination; the data were examined through thematic content analysis and coding aligned to core governance principles transparency, accountability, participation, and effectiveness supported by source triangulation. The findings indicate that the outlet has brought legality services closer to an island community by measuring and registering dozens of vessels under 7 GT, strengthening fishers’ legal identity, and facilitating access to subsidized diesel and basic safety support, while also promoting more standardized risk-prevention practices. However, implementation remains constrained by limited digital literacy among fishers, reliance on a small number of trained technical staff for measurement and data entry, and fragmented data management and coordination across KSOP, KPLP, and local government agencies, which reduces the consistency and scalability of accountability mechanisms.